ARE THE MEDIA SERVING BOKO HARAM TERRORIST ACTIVITIES IN NIGERIA? - OKECHUKWU GABRIEL MOWETE; CORNELIUS CHIEDOZIE OZEH (International Studies Journal)
This study investigates the intricate relationship between media, terrorism, and the Boko Haram sect in Nigeria. It specifically, analyses the unintentional facilitation of terrorism via media reportage in Nigeria with special focus on the Boko Haram sect. The complex dynamics between media portrayal, terrorist activities, and the broader socio-political landscape in the context of Boko Haram provides the backdrop for this investigation. Through a nuanced exploration and analysis of data collected from secondary sources guided by framing theory of communication studies, the study aims to shed light on the multifaceted interplay of media narratives, terrorism, and counterterrorism efforts, offering insights into the role of the media in shaping public perceptions and responses to the Boko Haram insurgency. The study recommended responsible journalism and fact-checking towards striking a balance between media roles and Boko Haram’s tactics.